Some Words Mispronunciation in Pro News Today at Pro News Radio - Difiani Apriyanti; Anggara Payudha (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
Learning English through media-printed media such as newspaper printed in English and electronic media such as Radio andTelevision present in English. In Padang, West Sumatra, Pro News Radio is one of the stations which broadcast an English program. It isnamed Pro News Today. Most of the listeners are people in West Sumatra who want to learn English. Because many people are hopingmuch from this program, it is a must to see whether the program is being presented perfectly. Referring to this reason, the writersconducted a project about mispronunciation words that occur by the newsreaders during broadcasting the news. By applying dictionaryreference.com the writers find out that they did mispronounce several words during broadcasting, and there were same words which aremispronounced by the two different newsreaders. The writers also did interview to the newsreaders whether they are aware of theirmistake or not. From their answer, it can be concluded that they do not realize that they have made the mistake. The writers hope that ProNews Radio gives more attention to the English skill of the newsreaders in English program.